Stenting in the common femoral vein does not increase posthrombotic syndrome or rethrombosis. (14th October 2021) - Krause, S; Telayna, J M J R; Costantini, R A; Telayna, J M
Abstract: Background: In lower limbs deep venous thrombosis (DVT) scenario there is evidence that favours catheter guided invasive treatment. The treatment with stenting in the common femoral vein could be related with a diminished permeability in the inflow of the deep femoral vein. There is scarce data of the clinical follow up of this treatment. Purpose: To analize and compare clinical and procedural outcomes in endovenous interventions that required stent placement in the common femoral vein because of residual lesion vs interventions that did no require such treatment. Methods: From May 2010 to December 2020, 122 endovenous interventions were performed, within these 74 were DVT compromising the iliofemoral territory. Two groups were defined: Group A 28 (38%) that required stent placement in the common femoral vein and Group B 46 (62%) that did not required such treatment. Results: Baseline characteristics were Group A vs Group B n (%) respectively: Median age 41.1±16.7 vs 40.5±18.8; female 23 (82) vs 27 (58); smoking 7 (25) vs 14 (30); cancer 1 (4) vs 7 (15); prior prolonged rest 7 (25) vs 14 (30); concomitant diagnosis of pulmonary embolism 7 (25) vs 17 (37). Within the female population 2 (7) vs 1 (2) were in puerperium; 6 (21) vs 6 (13) were under contraceptive therapy. Regarding the diagnosis of DVT 21 (75) vs 37 (80) were acute; 7 (25) vs 9 (19) were chronic. Compromised vessels were primitive iliac vein 21 (75) vs 38 (82); external iliac vein 6 (21) vs 18 (39); superficial femoral vein 11 (39) vs 8 (17); May-Thurner syndrome 14 (50) vs 20 (43). As regards the aspects of the intervention 15 (53) vs 34 (74) had a filter implanted in the inferior vena cava; thrombolytics were infused in 20 (71) vs 32 (70); manual thrombectomy was performed in 8 (27) vs 17 (37); mechanical thrombectomy 11 (39) vs 19 (41); pre dilation with balloon was performed in 22 (79) vs 39 (85); dedicated venous stents were implanted in 22 (78) vs 39 (85); not dedicated venous stents in 13 (46) vs 11 (24). Technique success was achieved in 28 (100) vs 45 (98) p=1; major bleeding occurred 0 vs 2 (4) p=0.5; rethrombosis 3 (10) vs 9 (20) p=0.25; intrahospital death 1 (4) vs 2 (4) p=1; early reintervention was needed 1 (4) vs 2 (4) p=1, radiation dose (min) 35.4±20.2 vs 30.1±17.0 p=0.2; Contrast (ml) 216.5±76.8 vs 217.3±90.8 p=0.9. During follow up (34.1±31.5 vs 22.3±16.4) image control was performed in 27 (96) vs 39 (85) p=0.23 with either doppler or chest computed tomography angiography. Post thrombotic syndrome (PTS) symptoms were classified with Villalta Score assuming that 0–4 points had no PTS, 5–9 points presented mild PTS, 10–14 points moderate PTS, >14 points severe PTS, in Group A 1 (4) presented mild PTS vs Group B 2 (4) mild PTS p=1, 1 (2) moderate PTS. Conclusions: Endovenous treatment with stent placement in the common femoral vein did not required more reinterventions nor had more complications nor had more PTS that the interventions without stent placement. FUNDunding Acknowledgement: Type of funding sources: None.